Tumor promoters stimulate hyperplasia of microtubule organizing center and inhibit DNA synthesis in cultured cells. - R N Mascardo; P Sherline (The Journal of Clinical Investigation, 1984)
Chemical tumor promoters induce significant morphologic changes in several cultured cell models. In this article we describe a new effect of two potent, chemically different tumor promoters, 12-O-tetradecanoylphorbol-13-acetate (TPA) and dihydroteleocidin B (DHTB) on cultured human HeLa and melanoma cells. Using immunofluorescence microscopy, we observed that TPA and DHTB induced a dramatic increase in the size (greater than or equal to 3X normal diameter) of the centrosome, a microtubule-organizing center, within 24 h of incubation. In HeLa cells the effect was serum- and dose-dependent, was observed in 76-92% of cells within 72 h of incubation, and was associated with an increase in cytoplasm-nucleus ratio and proliferation of microtubules from the centrosome. The tumor promoters inhibited serum-induced DNA synthesis in both cell lines. Electron microscopy revealed the presence of clumps of microcentriole bodies or fragments adjacent to the intact centriole. Images